STRATEGI PEMASARAN PRODUK-PRODUK GADAI SYARIAH DALAM MENINGKATKAN JUMLAH NASABAH DITINJAU DARI PERSPEKTIF ISLAM - Nelly Rahmatillah; Uswatun Hasanah (Jurnal Ekonomi Syariah Darussalam, 2020)
Pegadaian is a non-bank financial company that is often referred to as a company â€œOvercoming Problems without Problemsâ€ whose function is to help public finance urgent nature. This study aims to determine the marketing strategy of sharia pawn products at PT. Pegadaian (Persero) Syariah Simpang Lima Banyuwangi in marketing products sharia pawn Simpang Lima Banyuwangi in terms of perspective from Islam. This research data uses primary data using data. PT. Pegadaian (Persero) Syariah Simpang Lima Banyuwangi is legitimate because it is in accordance with promotions that are permitted in Islam and is related to the characteristics of the Prophet when he carried out promotions (marketing) and marketing strategy undertaken by PT. Pegadaian (Persero) Syariah Simpang Lima Banyuwangi is able to influence the growth in the number of promotional systems used by PT. Banyuwangi Syariah Pegadaian can be seen from the results of the SWOT analysis consisting of IFAS matrices namely strengths and weaknesses and the EFAS Matrix that is, opportunities and threats so that they will show the results of the SWOT.